Representative Stress-Strain Curve by Spherical Indentation on Elastic-Plastic Materials - Chao Chang; M. A. Garrido; J. Ruiz-Hervias; Zhu Zhang; Le-le Zhang (Advances in Materials Science and Engineering)
Tensile stress-strain curve of metallic materials can be determined by the representative stress-strain curve from the spherical indentation. Tabor empirically determined the stress constraint factor (stress CF), ψ, and strain constraint factor (strain CF), β, but the choice of value for ψ and β is still under discussion. In this study, a new insight into the relationship between constraint factors of stress and strain is analytically described based on the formation of Tabor’s equation. Experiment tests were performed to evaluate these constraint factors. From the results, representative stress-strain curves using a proposed strain constraint factor can fit better with nominal stress-strain curve than those using Tabor’s constraint factors.